2020
DOI: 10.1177/1479164120973676
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes, metformin and glucose lowering therapies after myocardial infarction: Insights from the SWEDEHEART registry

Abstract: Objective: To explore real-life use of glucose lowering drugs and prognosis after acute myocardial infarction (AMI) with a special focus on metformin. Methods: Patients ( n = 70270) admitted for AMI 2012–2017 were stratified by diabetes status and glucose lowering treatment and followed for mortality and MACE+ (AMI, heart failure (HF), stroke, mortality) until end of 2017 (mean follow-up time 3.4 ± 1.4 years) through linkage with national registries and SWEDEHEART. Hazard ratios (HR) were calculated in adjuste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…UK Prospective Diabetes Study (UKPDS) Group,” 1998). Ample observational evidence supports survival benefits in people with diabetes treated with metformin, including when compared to people without diabetes (Bannister et al, 2014; Campbell et al, 2017; Jong et al, 2019; Ritsinger et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…UK Prospective Diabetes Study (UKPDS) Group,” 1998). Ample observational evidence supports survival benefits in people with diabetes treated with metformin, including when compared to people without diabetes (Bannister et al, 2014; Campbell et al, 2017; Jong et al, 2019; Ritsinger et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…SGLT2i demonstrated the most robust clinical evidence for reduction of death from any cause and CVD, in patients with or without T2D, heart failure, and chronic kidney disease (CKD) (Cavender et al, 2018;Heerspink et al, 2020;Neal et al, 2017;Packer et al, 2020;Perkovic et al, 2019) Group," 1998). Ample observational evidence supports survival benefits in people with diabetes treated with metformin, including when compared to people without diabetes (Bannister et al, 2014;Campbell et al, 2017;Jong et al, 2019;Ritsinger et al, 2020).…”
Section: Mortalitymentioning
confidence: 99%
“…By screening for glucose disturbances in patients with AMI, lifestyle modification and pharmacological treatment can be initiated earlier. In a recently published register study, it was shown that patients with prediabetes treated with metformin have an improved outcome [ 21 ]. However, whether early lifestyle and medical interventions have a positive effect on short- and/or long-term outcome needs to be further established in randomised intervention studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Metformin (a) inhibits gluconeogenesis thus reducing blood sugar 27 and (b) helps activate pro-survival kinase AMPK which via mitochondria involved metabolic pathways results in cardiovascular health and lifespan improvement. 28 Triamcinolone, a synthetic glucocorticoid, is used to treat autoimmune diseases, asthma, rheumatoid and arthritic conditions. 29 , 30 , 31 The beta-lactam antibiotic, Amoxicillin, inhibits transpeptidation required for bacterial cell membrane synthesis.…”
Section: Discussionmentioning
confidence: 99%